(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
The dynamic moisture absorption of fractal polyester was studied at a constant temperature (30 °C) and humidity (80% RH). The model of heat and moisture transfer was then built based on the heat and mass transfer theories. Finite element method was used to solve the model. By comparing the moisture absorption predicted by the mechanism model and the experimental data, we concluded that variations trend of both were consistent. Besides, fields of temperature and humidity with different thickness of fractal polyester were predicted and analyzed by this model.